2009
DOI: 10.2478/s11535-009-0016-2
|View full text |Cite
|
Sign up to set email alerts
|

Brain monoamine oxidase A in hyperammonemia is regulated by NMDA receptors

Abstract: Mitochondrial enzyme monoamine oxidase A (MAO-A) generates hydrogen peroxide (H 2 O 2 ) and is up-regulated by Ca 2+ and presumably by ammonia. We hypothesized that MAO-A may be under the control of NMDA receptors in hyperammonemia. In this work, the in vivo effects of single dosing with ammonia and NMDA receptor antagonist MK-801 and the in vitro effect of Ca 2+ on MAO-A activity in isolated rat brain mitochondria were studied employing enzymatic procedure. Intraperitoneal injection of rats with ammonia led t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In addition, it would be interesting to follow-up on whether treating WT mice with a glucocorticoid receptor antagonist during the MS manipulation will prevent the development of the anxiety-like and depressive-like behaviors, and perturbations of the serotonergic system. Additionally, it has been found that MS affects NMDA receptor 1 expression (Sachs et al, 2013 ), and that there is evidence of interplay between MAO A and NMDA receptors (Kosenko and Kaminsky, 2009 ; Bortolato et al, 2012 ). Given these evidence, using this mouse model of early life environmental or pharmacological stress may also be useful in elucidating and understanding the effects of NMDA receptor antagonists, such as ketamine, which have recently demonstrated promise in the treatment of drug-resistant depression (Zarate et al, 2006 ; Autry et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it would be interesting to follow-up on whether treating WT mice with a glucocorticoid receptor antagonist during the MS manipulation will prevent the development of the anxiety-like and depressive-like behaviors, and perturbations of the serotonergic system. Additionally, it has been found that MS affects NMDA receptor 1 expression (Sachs et al, 2013 ), and that there is evidence of interplay between MAO A and NMDA receptors (Kosenko and Kaminsky, 2009 ; Bortolato et al, 2012 ). Given these evidence, using this mouse model of early life environmental or pharmacological stress may also be useful in elucidating and understanding the effects of NMDA receptor antagonists, such as ketamine, which have recently demonstrated promise in the treatment of drug-resistant depression (Zarate et al, 2006 ; Autry et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…In quantitative ratio, the main source of ammonia in the body is the oxidative deamination of amino acids with its key enzyme glutamate dehydrogenase [22]. Besides, reactions of the deamination of biogenic amines with the participation of mitochondrial monoamine oxidase also make a significant contribution to the replenishment of the endogenous ammonia pool [23]. Thus, glutamate dehydrogenase and monoamine oxidase reactions can be considered as the main biochemical mechanisms of ammonia formation in the organism.…”
Section: Furthermore (Nh 4 +mentioning
confidence: 99%